Composition for optical shaping

The photo-forming composition, specifically designed with a combination of polymerizable monomers, acidic compounds, phenol backbone compounds, and photopolymerization initiators, addresses the challenges of shape accuracy, toughness, water resistance, and color tone in optical three-dimensional shaping for dental applications, resulting in enhanced performance for dental mouthpieces and other medical devices.

JP7672983B2Active Publication Date: 2025-05-08KURARAY NORITAKE DENTAL
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021546993
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-18
Filing Date
2020-09-18
Publication Date
2025-05-08
Estimated Expiration
2040-09-18

AI Technical Summary

Technical Problem

Existing photocurable resin compositions for optical three-dimensional shaping, particularly in dental applications, face challenges in achieving excellent shape accuracy, toughness, water resistance, and color tone, due to issues like oxygen inhibition and strong light exposure.

Method used

A photo-forming composition comprising a polymerizable monomer without acidic groups, an organic compound with acidic groups, a compound with a phenol backbone, and a photopolymerization initiator, optimized in terms of component ratios and types to enhance shapeability, toughness, water resistance, and color tone.

Benefits of technology

The composition achieves excellent shapeability and mechanical properties, with improved toughness, water resistance, and color tone, making it suitable for dental mouthpieces, denture base materials, and sleep apnea treatment devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007672983000001
    Figure 0007672983000001
  • Figure 0007672983000002
    Figure 0007672983000002
Patent Text Reader

Abstract

The present invention provides a composition for photofabrication that, when shaped by photofabrication, has outstanding fabrication characteristics and results in outstanding toughness, water resistance, and color tone of a cured article. The present invention relates to a composition for photo fabrication, containing a polymerizable monomer (A) which does not have an acidic group, an organic compound (B) which has an acidic group, a compound (C) (not included in the organic compound (B) having an acidic group) which has a phenol skeleton and does not have a polymerizable group, and a photopolymerization initiator (D), the content of the compound (C) with the phenol skeleton having 0.5–500 parts by mass relative to 100 parts by mass of the organic compound (B) having an acidic group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for stereolithography. More specifically, the present invention is capable of producing a three-dimensional object having excellent formability, toughness, water resistance, and color tone when produced by stereolithography. The composition is particularly suitable for use as a dental mouthpiece or denture base material. [Background technology]

[0002] Patent Document 1 discloses a method for producing a three-dimensional object by repeating the steps of supplying a required amount of controlled light energy to a liquid photocurable resin to harden it into a thin layer, supplying further liquid photocurable resin on top of it, and then irradiating it with light under control to harden it into a thin layer, thereby so-called optical three-dimensional modeling. A basic practical method for this method was further proposed in Patent Document 2, and since then, numerous proposals have been made regarding optical three-dimensional modeling technology.

[0003] A typical method for optically manufacturing a three-dimensional object is a liquid tank stereolithography method, which is generally adopted, in which the liquid surface of a liquid photocurable resin composition in a container is selectively irradiated with a computer-controlled ultraviolet laser so as to obtain a desired pattern, cured to a predetermined thickness to form a cured layer, and then one layer of liquid photocurable resin composition is supplied onto the cured layer, and similarly irradiated with an ultraviolet laser to cure in the same manner as above to form a continuous cured layer, thereby repeating the lamination operation to manufacture a three-dimensional object of a final shape. This method has attracted much attention in recent years because it can easily and accurately manufacture a three-dimensional object of interest in a relatively short time, even if the shape of the object is quite complex.

[0004] The applications of the three-dimensional objects obtained by the stereolithography method have expanded from mere concept models to test models, prototypes, etc., and accordingly, the three-dimensional objects are increasingly required to have excellent modeling accuracy. In addition to such characteristics, they are also required to have excellent characteristics suited to the purpose. In particular, in the field of dental materials, dental mouthpieces and denture bases have different shapes for each individual patient and are complex in shape, so the application of the stereolithography method is expected.

[0005] Dental mouthpieces include those worn on the teeth to correct the alignment of teeth, called dental aligners, those worn on the teeth to correct jaw position, called dental splints, those worn on the teeth while sleeping at night to treat sleep apnea syndrome, those worn on the teeth to suppress tooth wear due to teeth grinding, and those worn in the oral cavity to reduce trauma caused by large external forces applied to the teeth or jawbone during contact sports and to protect the stomatognathic system and brain. In recent years, dental mouthpieces have been rapidly expanding in use in orthodontics due to their good aesthetics and the ability to be removed when desired. Sleep apnea syndrome is also a case that has attracted attention in the medical field, and their use as a treatment tool is rapidly increasing.

[0006] Denture base materials are materials used on the gums when dentures are worn due to tooth loss. In recent years, the demand for dentures has increased dramatically due to the increase in the elderly population.

[0007] These dental mouthpieces and denture base materials are commonly required to have toughness, water resistance, and good color tone. If the toughness is impaired, the wearing comfort will be poor, and external forces or occlusal impacts will be directly applied to the jawbone. If the material is easily broken, there is also the problem that it will need to be remade frequently. Furthermore, if the water resistance is impaired, there is the problem that the mechanical properties will decrease, the orthodontic force or shock absorption will be lost, and the material will be easily broken, making it unsuitable for practical use. If the color tone is poor, it will simply look bad.

[0008] In addition, when dental mouthpieces, denture base materials, and treatment tools for sleep apnea syndrome are usually produced, it is necessary to take an impression of the oral cavity, but problems such as the discomfort of the impression and the need for skill in technical operations have been pointed out. In recent years, due to the development of digital technology, attempts have been made to apply optical intraoral scanning to take impressions, and to apply optical three-dimensional modeling to molding. In modeling, a photocurable resin composition is used, but in particular in optical three-dimensional modeling, the composition is exposed to oxygen at each modeling step, and curing is particularly likely to be insufficient, and it has been difficult to achieve both mechanical strength, toughness, and water resistance. Furthermore, in optical three-dimensional modeling, stronger light is irradiated locally than in a general dental photopolymerization device, so that the components in the photocurable resin composition are more likely to oxidize or decompose during photomodeling, resulting in a problem of coloring of the three-dimensional object. Furthermore, due to the above-mentioned inhibition of curing by oxygen and irradiation of strong localized light, it is not easy to ensure a molding accuracy suitable for practical use in the case of complex shapes such as dental mouthpieces and denture base materials. Therefore, it has been difficult to obtain a photocurable resin composition as a whole that has excellent molding accuracy and a cured product that has excellent properties such as toughness and water resistance and also has a good color tone.

[0009] Against this background, for example, Patent Document 3 proposes a curable composition for photo-lithography that has a di(meth)acrylate having two aromatic rings and two (meth)acrylates, and a (meth)acrylic monomer having a carboxy group, as a technology that has excellent toughness and enables optical three-dimensional modeling. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 56-144478 [Patent Document 2] Japanese Patent Application Publication No. 60-247515 [Patent Document 3] International Publication No. 2017 / 061446 Summary of the Invention [Problem to be solved by the invention]

[0011] Patent Document 3 does not disclose anything about the modeling accuracy, water resistance, and color tone of the resin composition for optical three-dimensional modeling.

[0012] Therefore, an object of the present invention is to provide a stereolithography composition that has excellent shaping properties when shaped by stereolithography, and has excellent toughness, water resistance, and color tone of a cured product. Also, the present invention provides a stereolithography composition that is particularly suitable for dental mouthpieces, denture base materials, and treatment devices for sleep apnea syndrome. [Means for solving the problem]

[0013] That is, the present invention includes the following inventions. [1] A composition for stereolithography comprising a polymerizable monomer (A) having no acidic group, an organic compound (B) having an acidic group, a compound (C) having no polymerizable group and having a phenol skeleton (excluding those contained in the organic compound (B) having an acidic group), and a photopolymerization initiator (D), in which the content of the compound (C) having a phenol skeleton is 0.5 to 500 parts by mass per 100 parts by mass of the organic compound (B) having an acidic group; [2] The photopolymerization composition according to [1], wherein the polymerizable monomer (A) contains a monofunctional polymerizable monomer (A)-1; [3] The stereolithography composition according to [2], wherein the monofunctional polymerizable monomer (A)-1 contains a monofunctional polymerizable monomer (A)-1a having a cyclic structure; [4] The composition for stereolithography according to any one of [1] to [3], wherein the polymerizable monomer (A) contains a multifunctional polymerizable monomer (A)-2; [5] The photopolymerization composition according to [4], wherein the polyfunctional polymerizable monomer (A)-2 is a polyfunctional polymerizable monomer (A)-2a having a urethane bond; [6] The stereolithography composition according to [5], wherein the polyfunctional polymerizable monomer (A)-2a having a urethane bond is a (meth)acrylate having, in one molecule, at least one structure selected from the group consisting of polyester, polycarbonate, polyurethane, polyether, polyconjugated diene, and hydrogenated polyconjugated diene, and a urethane bond; [7] The stereolithography composition according to [5], wherein the polyfunctional polymerizable monomer (A)-2a having a urethane bond is at least one polyol moiety selected from the group consisting of polyesters having a structure derived from an aliphatic diol unit having 4 to 18 carbon atoms and a branched structure in one molecule, polycarbonates, polyurethanes, polyethers, polyconjugated dienes, and hydrogenated polyconjugated dienes, and a (meth)acrylate having a urethane bond; [8] The composition for stereolithography according to any one of [1] to [7], wherein the organic compound (B) having an acidic group contains an organic compound (B)-1 having an acidic group and no polymerizable group; [9] The stereolithography composition according to [8], wherein the organic compound (B)-1 having an acidic group and no polymerizable group is at least one selected from the group consisting of a carboxylic acid compound having only one carboxy group as the acidic group, a dicarboxylic acid compound having only two carboxy groups as the acidic groups, and a carboxylic acid compound having a hydroxyl group and a carboxy group;

[10] The stereolithography composition according to [8], wherein the organic compound (B)-1 having an acidic group and no polymerizable group is at least one selected from the group consisting of isoeicosane diacid, DL-lactic acid, malic acid, tartaric acid, citric acid, and benzoic acid;

[11] The composition for stereolithography according to any one of [1] to

[10] , wherein the organic compound (B) having an acidic group contains an organic compound (B)-2 having an acidic group and a polymerizable group;

[12] The photopolymerization composition according to

[11] , wherein the organic compound (B)-2 having an acidic group and a polymerizable group is a carboxy group-containing polymerizable monomer;

[13] The composition for stereolithography according to

[12] , wherein the carboxy group-containing polymerizable monomer is at least one selected from the group consisting of (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxyethyl phthalic acid, (meth)acryloyloxyethyl hexahydrophthalic acid, (meth)acryloyloxypropyl phthalic acid, and (meth)acryloyloxypropyl hexahydrophthalic acid;

[14] The composition for stereolithography according to any one of [1] to

[13] , wherein the compound (C) having a phenol skeleton is a phenol compound having only an aromatic monocyclic ring or an aromatic fused bicyclic ring as a cyclic structure;

[15] The composition for stereolithography according to any one of [1] to

[13] , wherein the compound (C) having a phenol skeleton is at least one selected from the group consisting of pt-butylphenol, biphenol, 2-phenylpropylphenol, 4-methoxyphenol, 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-methoxyphenol, 2,4,6-trimethylphenol, 2,6-di-isopropylphenol, and naphthol;

[16] A dental material comprising a cured product of the stereolithography composition according to any one of [1] to

[15] ;

[17] A dental mouthpiece comprising a cured product of the stereolithography composition according to any one of [1] to

[15] ;

[18] A denture base material comprising a cured product of the stereolithography composition according to any one of [1] to

[15] ;

[19] A material for treating a sleep disorder, comprising a cured product of the composition for stereolithography according to any one of [1] to

[15] ;

[20] A method for producing a three-dimensional object by a stereolithography method using the composition for stereolithography according to any one of [1] to

[15] . Effect of the Invention

[0014] The photopolymerization composition of the present invention has excellent moldability when molded by photopolymerization, and the cured product has excellent toughness, water resistance, and color tone, and can therefore be suitably used for intraoral applications such as various dental materials (particularly dental mouthpieces and denture base materials) or various sleep disorder treatment materials (particularly treatment devices for sleep apnea syndrome). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The stereolithography composition of the present invention contains a polymerizable monomer (A) having no acidic group, an organic compound (B) having an acidic group, a compound (C) having no polymerizable group and having a phenol skeleton (excluding those contained in the organic compound (B) having an acidic group), and a photopolymerization initiator (D), and the content of the compound (C) having a phenol skeleton is 0.5 to 500 parts by mass relative to 100 parts by mass of the organic compound (B) having an acidic group. Note that in this specification, the upper and lower limits of the numerical ranges (contents of each component, values ​​calculated from each component, and each physical property, etc.) can be appropriately combined.

[0016] [Polymerizable monomer (A) having no acidic group] A radical polymerizable monomer is preferably used as the polymerizable monomer (A) having no acidic group used in the stereolithography composition of the present invention. Specific examples of the radical polymerizable monomer in the polymerizable monomer (A) having no acidic group include (meth)acrylate polymerizable monomers; (meth)acrylamide polymerizable monomers; esters such as α-cyanoacrylic acid, (meth)acrylic acid, α-halogenated acrylic acid, crotonic acid, cinnamic acid, sorbic acid, maleic acid, and itaconic acid; vinyl esters; vinyl ethers; mono-N-vinyl derivatives; and styrene derivatives. Among these, from the viewpoint of curability, (meth)acrylate polymerizable monomers and (meth)acrylamide polymerizable monomers are preferred. These may be used alone or in combination of two or more. In this specification, the term "polymerizable group" refers to a polymerizable functional group possessed by the polymerizable monomer, and examples thereof include a vinyl group, a vinyloxy group, a (meth)acryloyl group, a (meth)acryloyloxy group, a (meth)acrylamide group, etc. Among these polymerizable groups, an acryloyloxy group and a methacryloyloxy group are preferred.

[0017] Examples of the polymerizable monomer (A) having no acidic group in the present invention include monofunctional polymerizable monomer (A)-1 and polymerizable monomer (A)-2 having multiple polymerizable groups (hereinafter also referred to as "polyfunctional polymerizable monomer (A)-2"). From the viewpoint of easy low viscosity, monofunctional polymerizable monomer (A)-1 is preferred, from the viewpoint of curability, polymerizable monomer (A)-2 having multiple polymerizable groups is preferred, and further from the viewpoint of toughness, it is preferred to use both monofunctional polymerizable monomer (A)-1 and polyfunctional polymerizable monomer (A)-2. In the present invention, the ratio of the monofunctional polymerizable monomer (A)-1 to the polyfunctional polymerizable monomer (A)-2 [(A-1) / (A-2)] is preferably 10 / 90 to 90 / 10, more preferably 15 / 85 to 75 / 25, even more preferably 20 / 80 to 60 / 40, and particularly preferably 25 / 75 to 45 / 55, from the viewpoint of curability and toughness. In this specification, "monofunctional" means having one polymerizable group. In addition, in this specification, the expression "(meth)acryloyl" is used to mean both methacryloyl and acryloyl, and the same applies to the expressions similar thereto, such as "(meth)acryl" and "(meth)acrylate".

[0018] The monofunctional polymerizable monomer (A)-1 includes a monofunctional polymerizable monomer (A)-1a having a cyclic structure and a monofunctional polymerizable monomer (A)-1b not having a cyclic structure, and from the viewpoint of curability and toughness, it is preferable to contain a monofunctional polymerizable monomer (A)-1a having a cyclic structure. The monofunctional polymerizable monomer (A)-1 may contain a monofunctional fluorine-containing (meth)acrylate polymerizable monomer.

[0019] The cyclic structure is not particularly limited as long as it exerts the effects of the present invention, and examples thereof include aromatic monocyclic rings such as a benzene ring, a biphenyl ring, and a triphenylmethyl ring; aromatic condensed bicyclic rings such as a naphthalene ring, a pentalene ring, an indene ring, an indane ring, a tetralin ring, and an azulene ring; as-indacene ring, an s-indacene ring, an acenaphthylene ring, an acenaphthene ring, a fluorene ring, a phenalene ring, a perinaphthene ring, a phenanthrene ring, and an anthracene ring. Carbohydrate condensed tricyclic rings; saturated hydrocarbon rings such as norbornane ring, tetracyclododecanyl ring, adamantane ring, dicyclopentenyl ring, tricyclododecanyl ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, cyclooctane ring, and cyclodecane ring; unsaturated hydrocarbon rings such as norbornene ring, tetralin ring, and fluorene ring; saturated monocyclic rings having one nitrogen atom such as pyrrolidine ring and piperidine ring; and nitrogen-containing rings such as piperazine ring and methenamine ring. unsaturated monocyclic rings having two or more nitrogen atoms, such as a pyrrole ring or a pyridine ring; unsaturated monocyclic rings having two or more nitrogen atoms, such as an imidazole ring, an indazole ring, an imidazoline ring, a pyrazole ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, or a tetrazole ring; unsaturated polycyclic rings having one nitrogen atom, such as an indole ring, an isoindole ring, a quinoline ring, an isoquinoline ring, or a carbazole ring; heterocyclic rings having only a nitrogen atom, such as an unsaturated polycyclic ring having two or more nitrogen atoms, such as a benzimidazole ring, a purine ring, a benzotriazole ring, or a choline ring; heterocyclic rings having both a nitrogen atom and an oxygen atom, such as a morpholine ring, a lactam ring, an oxazole ring, a benzoxazine ring, a hydantoin ring, or a phthalocyanine ring; and heterocyclic rings having both a nitrogen atom and a sulfur atom, such as a thiazole ring, a thiazine ring, or a phenothiazine ring. Among these, from the viewpoints of curability and the toughness and water resistance of the cured product of the resulting stereolithography composition, preferred are aromatic monocyclic rings, aromatic condensed bicyclic rings, condensed carbocyclic rings, saturated hydrocarbon rings, unsaturated hydrocarbon rings, saturated monocyclic rings having one nitrogen atom, and heterocyclic rings having both a nitrogen atom and an oxygen atom, more preferred are aromatic monocyclic rings, aromatic condensed bicyclic rings, saturated hydrocarbon rings, unsaturated hydrocarbon rings, and saturated monocyclic rings having one nitrogen atom, and even more preferred are aromatic monocyclic rings, saturated hydrocarbon rings, unsaturated hydrocarbon rings, and saturated monocyclic rings having one nitrogen atom.

[0020] Examples of the monofunctional polymerizable monomer (A)-1a having a cyclic structure include o-phenylphenol(meth)acrylate, m-phenylphenol(meth)acrylate, p-phenylphenol(meth)acrylate, methoxylated-o-phenylphenol(meth)acrylate, methoxylated-m-phenylphenol(meth)acrylate, methoxylated-p-phenylphenol(meth)acrylate, ethoxylated-o-phenylphenol(meth)acrylate, ethoxylated-m-phenylphenol(meth)acrylate, ethoxylated propoxylated-o-phenylphenol (meth)acrylate, propoxylated-m-phenylphenol (meth)acrylate, propoxylated-p-phenylphenol (meth)acrylate, butoxylated-o-phenylphenol (meth)acrylate, butoxylated-m-phenylphenol (meth)acrylate, butoxylated-p-phenylphenol (meth)acrylate, o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, p-phenylphenol Phenoxybenzyl (meth)acrylate, 2-(o-phenoxyphenyl)ethyl (meth)acrylate, 2-(m-phenoxyphenyl)ethyl (meth)acrylate, 2-(p-phenoxyphenyl)ethyl (meth)acrylate, 3-(o-phenoxyphenyl)propyl (meth)acrylate, 3-(m-phenoxyphenyl)propyl (meth)acrylate, 3-(p-phenoxyphenyl)propyl (meth)acrylate, 4-(o-phenoxyphenyl)butyl (meth)acrylate, 4-(m-phenoxyphenyl)butyl (meth)acrylates having an aromatic ring, such as 4-(p-phenoxyphenyl)butyl (meth)acrylate, phenyl (meth)acrylate, 4-biphenylyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, anthryl (meth)acrylate, o-2-propenylphenyl (meth)acrylate, benzhydrol (meth)acrylate, cumylphenol (meth)acrylate, fluorenyl (meth)acrylate, and fluorenylmethyl (meth)acrylate;2-(1-adamantyl)propyl (meth)acrylate, 2-methyladamantyl-2-yl (meth)acrylate, 2-ethyladamantyl-2-yl (meth)acrylate, 2-n-propyladamantyl-2-yl (meth)acrylate, 2-isopropyladamantyl-2-yl (meth)acrylate, 1-(adamantan-1-yl)-1-methylethyl (meth)acrylate, 1-(adamantan-1-yl)-1-ethyl (meth)acrylate alicyclic (meth)acrylic acid esters such as ethyl, 1-(adamantan-1-yl)-1-methylpropyl (meth)acrylate, and 1-(adamantan-1-yl)-1-ethylpropyl (meth)acrylate; cyclic (meth)acrylic acid esters having a nitrogen atom such as pentamethylpiperidinyl (meth)acrylate, tetramethylpiperidinyl (meth)acrylate, and 4-(pyrimidin-2-yl)piperazin-1-yl (meth)acrylate;Examples of the cyclic (meth)acrylamides include N-acryloylmorpholine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylpiperidine, N-(meth)acryloyl-2-methylpiperidine, and N-(meth)acryloyl-2,2,6,6-tetramethylpiperidine. Among these, from the viewpoint of excellent toughness and water resistance of the cured product of the stereolithography composition of the present invention, o-phenoxybenzyl acrylate, m-phenoxybenzyl acrylate, p-phenoxybenzyl acrylate, 2-(o-phenoxyphenyl)ethyl acrylate, 2-(m-phenoxyphenyl)ethyl acrylate, 2-(p-phenoxyphenyl)ethyl acrylate, fluorenyl (meth)acrylate, fluorenylmethyl (meth)acrylate, phenyl (meth)acrylate, 4-biphenylyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, anthryl (meth)acrylate, benzhydrol (meth)acrylate, cumylphenol (meth)acrylate, N-acryloylmorpholine, piperidyl acrylamide, tetramethylpiperidyl acrylamide, pentamethylpiperidinyl (meth)acrylate, tetramethylpiperidinyl (Meth)acrylates are preferred, m-phenoxybenzyl acrylate, 2-(o-phenoxyphenyl)ethyl acrylate, fluorenyl (meth)acrylate, fluorenylmethyl (meth)acrylate, 4-biphenylyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, benzhydrol (meth)acrylate, cumylphenol (meth)acrylate, piperidyl acrylamide, tetramethylpiperidyl acrylamide, pentamethylpiperidinyl (meth)acrylate, and tetramethylpiperidinyl (meth)acrylate are preferred, and m-phenoxybenzyl acrylate, 2-(o-phenoxyphenyl)ethyl acrylate, fluorenyl (meth)acrylate, fluorenylmethyl (meth)acrylate, 4-biphenylyl (meth)acrylate, piperidyl acrylamide, and tetramethylpiperidyl acrylamide are more preferred. These may be used alone or in combination of two or more.

[0021] Examples of the monofunctional polymerizable monomer (A)-1b that does not have a cyclic structure include undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, palmitoleic (meth)acrylate, heptadecyl (meth)acrylate, oleyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, glycerol mono(meth)acrylate, and erythritol mono(meth)acrylate. These may be used alone or in combination of two or more.

[0022] The content of the monofunctional polymerizable monomer (A)-1 in the photopolymerization composition of the present invention is preferably 1 to 90 mass% of the total amount of polymerizable monomers, and from the viewpoint of superior moldability and toughness and water resistance of the cured product, is more preferably 2 to 80 mass%, and even more preferably 3 to 70 mass%.

[0023] Examples of the polyfunctional polymerizable monomer (A)-2 include bifunctional polymerizable monomers and trifunctional or higher polyfunctional polymerizable monomers. From the viewpoint of toughness of the cured product, bifunctional polymerizable monomers are preferred.

[0024] Examples of bifunctional polymerizable monomers include (meth)acrylic acid ester compounds such as 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (commonly known as "Bis-GMA"), 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, and 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (commonly known as "UDMA"). Among these, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate is preferred because of its excellent curability and mechanical strength of the cured product.

[0025] Examples of the trifunctional or higher polymerizable monomer include (meth)acrylic acid ester compounds such as dipentaerythritol penta(meth)acrylate, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetra(meth)acrylate, and 1,7-diacryloyloxy-2,2,6,6-tetra(meth)acryloyloxymethyl-4-oxaheptane.

[0026] Further, the polyfunctional polymerizable monomer (A)-2 may be a polyfunctional polymerizable monomer (A)-2a having a urethane bond or a polyfunctional polymerizable monomer (A)-2b having no urethane bond. From the viewpoints of curability and toughness, it is preferable to contain a polyfunctional polymerizable monomer (A)-2a having a urethane bond.

[0027] Regarding the method for producing the polyfunctional polymerizable monomer (A)-2a having a urethane bond, the case where the polyfunctional polymerizable monomer (A)-2a having a urethane bond is a urethane-modified (meth)acrylic compound having a urethane bond (hereinafter, also simply referred to as "urethane-modified (meth)acrylic compound") will be described below. The urethane-modified (meth)acrylic compound can be easily synthesized, for example, by addition reaction of a polyol having a polymer skeleton described later, a compound having an isocyanate group (-NCO), and a (meth)acrylic compound having a hydroxyl group (-OH). The urethane-modified (meth)acrylic compound can also be easily synthesized by ring-opening addition reaction of a (meth)acrylic compound having a hydroxyl group with a lactone or alkylene oxide, and then addition reaction of the resulting compound having a hydroxyl group at one end with a compound having an isocyanate group.

[0028] The polyfunctional polymerizable monomer (A)-2a having a urethane bond is preferably a (meth)acrylate having, in one molecule, at least one structure (polymer skeleton) selected from the group consisting of polyesters, polycarbonates, polyurethanes, polyethers, polyconjugated dienes, and hydrogenated polyconjugated dienes, and a urethane bond, and more preferably a (meth)acrylate having, in one molecule, at least one polyol moiety selected from the group consisting of polyesters, polycarbonates, polyurethanes, polyethers, polyconjugated dienes, and hydrogenated polyconjugated dienes, each of which has a structure derived from an aliphatic diol unit having 4 to 18 carbon atoms and a branched structure, and a urethane bond. In the above structure, examples of the polyester include a polymer of a dicarboxylic acid (aromatic dicarboxylic acid such as phthalic acid or isophthalic acid; unsaturated aliphatic dicarboxylic acid such as maleic acid) and an aliphatic diol having 2 to 18 carbon atoms, a polymer of a dicarboxylic acid (saturated aliphatic dicarboxylic acid such as adipic acid or sebacic acid) and an aliphatic diol having 2 to 18 carbon atoms, a polymer of β-propiolactone, a polymer of γ-butyrolactone, a polymer of δ-valerolactone, a polymer of ε-caprolactone, and copolymers thereof. Of these, a polymer of a dicarboxylic acid (aromatic dicarboxylic acid such as phthalic acid or isophthalic acid; unsaturated aliphatic dicarboxylic acid such as maleic acid) and an aliphatic diol having 2 to 12 carbon atoms, and a polymer of a dicarboxylic acid (saturated aliphatic dicarboxylic acid such as adipic acid or sebacic acid) and an aliphatic diol having 2 to 12 carbon atoms are preferred. Examples of the polycarbonate include polycarbonates derived from an aliphatic diol having 2 to 18 carbon atoms, polycarbonates derived from bisphenol A, and polycarbonates derived from an aliphatic diol having 2 to 18 carbon atoms and bisphenol A, and preferred are polycarbonates derived from an aliphatic diol having 2 to 12 carbon atoms, polycarbonates derived from bisphenol A, and polycarbonates derived from an aliphatic diol having 2 to 12 carbon atoms and bisphenol A. Examples of the polyurethane include polymers of an aliphatic diol having 2 to 18 carbon atoms and a diisocyanate having 1 to 18 carbon atoms, and preferred are polymers of an aliphatic diol having 2 to 12 carbon atoms and a diisocyanate having 1 to 12 carbon atoms.Examples of polyethers include polyethylene glycol, polypropylene glycol, polybutylene glycol, and poly(1-methylbutylene glycol). Examples of polyconjugated dienes and hydrogenated polyconjugated dienes include 1,4-polybutadiene, 1,2-polybutadiene, polyisoprene, poly(butadiene-isoprene), poly(butadiene-styrene), poly(isoprene-styrene), polyfarnesene, and hydrogenated products thereof. Among these, polyester structures are preferred because of their excellent toughness.

[0029] Examples of compounds having an isocyanate group include hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), trimethylhexamethylene diisocyanate (TMHMDI), tricyclodecane diisocyanate (TCDDI), and adamantane diisocyanate (ADI).

[0030] Examples of the (meth)acrylic compound having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerin mono(meth)acrylate, and 2-hydroxy-3-acryloyloxypropyl (meth)acrylate. hydroxy(meth)acrylate compounds such as dipentaerythritol tri(meth)acrylate, 2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane, 1,2-bis[3-(meth)acryloyloxy-2-hydroxypropoxy]ethane, pentaerythritol tri(meth)acrylate, and dipentaerythritol tri- or tetra(meth)acrylate; and hydroxy(meth)acrylamide compounds such as N-hydroxyethyl(meth)acrylamide and N,N-bis(2-hydroxyethyl)(meth)acrylamide.

[0031] Examples of the aliphatic diol unit having a branched structure and having 4 to 18 carbon atoms include 2-methyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 1,3-butanediol, 2-methyl-1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 2,7-dimethyl-1,8-octanediol, 2-methyl-1,9-nonanediol, 2,8-dimethyl-1,9-nonanediol, 2-methyl-1,10-decanediol, 2,9-dimethyl-1,10-decanediol, and 2-methyl-1,11-undecanediol. Examples of the dimethyl-1,15-pentadecanediol include 2,14-dimethyl-1,15-pentadecanediol, 2,14-dimethyl-1,15-pentadecanediol, 2-methyl-1,16-hexadecanediol, and 2,15-dimethyl-1,16-hexadecanediol. Among these, from the viewpoint of the excellent curability and low viscosity of the stereolithography composition, it is preferable to use an aliphatic diol having 5 to 12 carbon atoms and a methyl group as a side chain, such as 2-methyl-1,4-butanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 2,7-dimethyl-1,8-octanediol, 2-methyl-1,9-nonanediol, or 2,8-dimethyl-1,9-nonanediol, as the polyol, more preferably 2-methyl-1,4-butanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, or 2,7-dimethyl-1,8-octanediol, and even more preferably 3-methyl-1,5-pentanediol or 2-methyl-1,8-octanediol.

[0032] The addition reaction between a compound having an isocyanate group and a (meth)acrylic compound having a hydroxyl group can be carried out according to a known method, and there is no particular limitation.

[0033] The obtained urethane-modified (meth)acrylic compound may be a reaction product of any combination of a polyol having at least one structure selected from the group consisting of polyester, polycarbonate, polyurethane, polyether, polyconjugated diene, and hydrogenated polyconjugated diene, a compound having an isocyanate group, and a (meth)acrylic compound having a hydroxyl group.

[0034] The weight average molecular weight (Mw) of the polyfunctional polymerizable monomer (A)-2a having a urethane bond is, from the viewpoints of viscosity and mechanical strength, preferably 500 to 30000, more preferably 1000 to 15000, even more preferably 1200 to 9000, even more preferably 1200 to 8000, particularly preferably 1500 to 7000, and most preferably 1500 to 5000. In the present invention, the weight average molecular weight (Mw) means a polystyrene-equivalent weight average molecular weight determined by gel permeation chromatography (GPC).

[0035] The content of the polyfunctional polymerizable monomer (A)-2a having a urethane bond in the photopolymerization composition of the present invention is preferably 10 to 95 mass% of the total amount of polymerizable monomers, and from the viewpoint of superior moldability and toughness and water resistance of the cured product, it is more preferably 20 to 90 mass%, and even more preferably 30 to 85 mass%.

[0036] Examples of the polyfunctional polymerizable monomer (A)-2b having no urethane bond include 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (commonly known as "Bis-GMA"), 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 2,2- Bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxy acryloyloxytriethoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, 1,4-bis(2-(meth)acryloyloxyethyl)pyromellitate, glycerol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol Di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-ethyl-1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,Examples of the acrylates include 10-decanediol di(meth)acrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethane, and tricyclodecane dimethanol di(meth)acrylate.

[0037] Examples of the trifunctional or higher polymerizable monomer include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, 1,7-diacryloyloxy-2,2,6,6-tetra(meth)acryloyloxymethyl-4-oxaheptane, and the like.

[0038] The content of the polyfunctional polymerizable monomer (A)-2b not having a urethane bond in the optical molding composition of the present invention is preferably 0 to 40 mass% of the total amount of polymerizable monomers, and from the viewpoint of superior toughness and water resistance of the cured product, is more preferably 1 to 30 mass%, and even more preferably 2 to 20 mass%.

[0039] The content of the polymerizable monomer (A) having no acidic group in the optical molding composition of the present invention is preferably 85 to 99 mass %, more preferably 88 to 95 mass %, and even more preferably 90 to 93 mass %.

[0040] [Organic compounds having acidic groups (B)] The stereolithography composition of the present invention contains an organic compound (B) having an acidic group. When a compound having an active proton such as a hydroxyl group, an amino group, an allylic hydrogen, a benzylic hydrogen, or an α-position hydrogen of a carbonyl group is present in the stereolithography composition, the basicity of the composition is strengthened, and the active proton is polarized, making the compounds in the composition more likely to undergo oxidation reactions or changing the resonance structure, which makes the stereolithography composition more likely to become colored. The organic compound (B) having an acidic group has the effect of reducing and stabilizing the polarization of the active hydrogen of a compound containing an active proton, and therefore can suppress the coloring of the stereolithography composition.

[0041] In the present invention, examples of the acidic group include a carboxy group, a phosphoric acid group, a pyrophosphoric acid group, a thiophosphoric acid group, a phosphonic acid group, a sulfonic acid group, a sulfinic acid group, a boronic acid group, and a silanol group. The organic compound (B) having an acidic group may have one type of acidic group alone, or may have two or more types of acidic groups. Examples of the organic compound (B) having an acidic group include an organic compound having a carboxy group, an organic compound having a phosphoric acid group, an organic compound having a sulfonic acid group, an organic compound having a sulfinic acid group, an organic compound having a boronic acid group, an organic compound having a silanol group, and an organic compound having a carboxy group and a phosphoric acid group. Among these, from the viewpoint of excellent color tone of the cured product, an organic compound having a carboxy group, an organic compound having a phosphoric acid group, and an organic compound having a sulfonic acid group are preferred, an organic compound having a carboxy group and an organic compound having a phosphoric acid group are more preferred, and an organic compound having a carboxy group is even more preferred. The organic compound (B) having an acidic group may be used alone or in combination of two or more types.

[0042] Examples of the organic compound (B) having an acidic group include an organic compound (B)-1 having an acidic group but not a polymerizable group, and an organic compound (B)-2 having an acidic group and a polymerizable group. From the viewpoint of a good color tone of the cured product, the organic compound (B)-1 having an acidic group but not a polymerizable group is preferably used. From the viewpoint of the toughness and water resistance of the cured product, the organic compound (B)-2 having an acidic group and a polymerizable group is preferably used. Furthermore, from the viewpoints of color tone, toughness and water resistance, it is preferable to use both the organic compound (B)-1 having an acidic group but not a polymerizable group, and the organic compound (B)-2 having an acidic group and a polymerizable group.

[0043] Examples of the organic compound (B)-1 having an acidic group but no polymerizable group include monocarboxylic acid compounds having only one carboxy group as an acidic group, dicarboxylic acid compounds having only two carboxy groups as acidic groups, carboxylic acid compounds having a hydroxyl group and a carboxy group, phosphate esters, and organic compounds having a sulfonic acid group. Examples of the monocarboxylic acid compounds having only one carboxy group as an acidic group include formic acid; aliphatic compounds such as acetic acid, butyric acid, valeric acid, stearic acid, oleic acid, and linoleic acid; and aromatic compounds such as benzoic acid. Examples of the dicarboxylic acid compounds having only two carboxy groups as acidic groups include aromatic compounds such as phthalic acid; and aliphatic compounds such as oxalic acid, succinic acid, maleic acid, fumaric acid, adipic acid, eicosane diacid, isoeicosane diacid, isodocosane diacid, eicosadienedioic acid, and isodocosadienedioic acid. Examples of the carboxylic acid compound having a hydroxyl group and a carboxyl group include aliphatic compounds such as glycolic acid, DL-lactic acid, malic acid, tartaric acid, and citric acid; and aromatic compounds such as salicylic acid. The number of hydroxyl groups in the carboxylic acid compound having a hydroxyl group and a carboxyl group is not particularly limited as long as it is 1 or more, but is preferably 1 to 5, more preferably 1 to 3, and even more preferably 1 to 2. Examples of the phosphoric acid ester include phosphoric acid monoesters such as ethyl phosphoric acid ester, butyl phosphoric acid ester, 2-ethylhexyl phosphoric acid ester, cyclohexyl phosphoric acid ester, and phenyl phosphoric acid ester; phosphoric acid diesters such as diethyl phosphoric acid ester, dibutyl phosphoric acid ester, di(2-ethylhexyl) phosphoric acid ester, dicyclohexyl phosphoric acid ester, and diphenyl phosphoric acid ester; and alkyl phosphoric acid triesters such as triethyl phosphate. Examples of the organic compound having a sulfonic acid group include aliphatic compounds such as methanesulfonic acid; and aromatic compounds such as benzenesulfonic acid, p-toluenesulfonic acid, and dodecylsulfuric acid.Among these, from the viewpoint of excellent color tone and little odor of the cured product, stearic acid, oleic acid, linoleic acid, benzoic acid, succinic acid, maleic acid, fumaric acid, phthalic acid, eicosane diacid, isoeicosane diacid, eicosadienedioic acid, glycolic acid, DL-lactic acid, malic acid, tartaric acid, citric acid, are preferred, isoeicosane diacid, DL-lactic acid, malic acid, tartaric acid, citric acid, benzoic acid are more preferred, and DL-lactic acid and benzoic acid are even more preferred. These may be used alone or in combination of two or more.

[0044] The content of the organic compound (B)-1 having an acidic group but not a polymerizable group in the stereolithography composition of the present invention is preferably 0.1 to 10% by mass relative to the total amount of polymerizable monomers, more preferably 0.25 to 5% by mass, and even more preferably 0.5 to 2.5% by mass, in terms of superior color tone and water resistance of the cured product. The content of the organic compound (B)-1 having an acidic group but not a polymerizable group is preferably 0.1 to 10% by mass in the entire stereolithography composition, more preferably 0.25 to 5% by mass, and even more preferably 0.5 to 3% by mass, in terms of superior color tone and water resistance of the cured product.

[0045] As the organic compound (B)-2 having an acidic group and a polymerizable group, a radical polymerizable monomer is suitably used. Specific examples of the radical polymerizable monomer in the organic compound (B)-2 having an acidic group and a polymerizable group include (meth)acrylate-based polymerizable monomers; (meth)acrylamide-based polymerizable monomers; esters such as α-cyanoacrylic acid, (meth)acrylic acid, α-halogenated acrylic acid, crotonic acid, cinnamic acid, sorbic acid, maleic acid, and itaconic acid; vinyl esters; vinyl ethers; mono-N-vinyl derivatives; and styrene derivatives. Among these, from the viewpoint of curability, (meth)acrylate-based polymerizable monomers and (meth)acrylamide-based polymerizable monomers are preferred. These may be used alone or in combination of two or more.

[0046] Examples of the organic compound (B)-2 having an acidic group and a polymerizable group include carboxy group-containing polymerizable monomers such as (meth)acrylic acid, (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxyethyl phthalic acid, (meth)acryloyloxyethyl tetrahydrophthalic acid, (meth)acryloyloxyethyl hexahydrophthalic acid, (meth)acryloyloxypropyl phthalic acid, (meth)acryloyloxypropyl tetrahydrophthalic acid, (meth)acryloyloxypropyl hexahydrophthalic acid, and 4-(meth)acryloyloxyethyl trimellitate; 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxyethyl trimethylol phosphate, and the like. - (meth) acryloyloxy butyl dihydrogen phosphate, 5- (meth) acryloyloxy pentyl dihydrogen phosphate, 6- (meth) acryloyloxy hexyl dihydrogen phosphate, 7- (meth) acryloyloxy heptyl dihydrogen phosphate, 8- (meth) acryloyloxy octyl dihydrogen phosphate, 9- (meth) acryloyloxy nonyl dihydrogen phosphate, 10- (meth) acryloyloxy decyl dihydrogen phosphate, 11- (meth) acryloyloxy undecyl dihydrogen phosphate, 12- (meth) acryloyloxy dodecyl dihydrogen phosphate, and other phosphate group-containing polymerizable monomers.Among these, from the viewpoint of excellent color tone and toughness of the cured product, (meth)acrylic acid, (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxyethyl phthalic acid, (meth)acryloyloxyethyl tetrahydrophthalic acid, (meth)acryloyloxyethyl hexahydrophthalic acid, (meth)acryloyloxypropyl phthalic acid, (meth)acryloyloxypropyl tetrahydrophthalic acid, (meth)acryloyloxypropyl hexahydrophthalic acid, 4-(meth)acryloyloxyethyl trimellitate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, and 10-(meth)acryloyloxydecyl dihydrogen phosphate are preferred, and from the viewpoints of excellent compatibility with low-polarity monomers, less reduction in water resistance, and less odor, (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxyethyl phthalic acid, (meth)acryloyloxyethyl tetrahydrophthalic acid, (meth)acryloyloxypropyl hexahydrophthalic acid, 4-(meth)acryloyloxyethyl trimellitate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, and 10-(meth)acryloyloxydecyl dihydrogen phosphate are preferred. More preferred are acryloyloxyethyl succinic acid, (meth)acryloyloxyethyl phthalic acid, (meth)acryloyloxyethyl tetrahydrophthalic acid, (meth)acryloyloxyethyl hexahydrophthalic acid, (meth)acryloyloxypropyl phthalic acid, (meth)acryloyloxypropyl tetrahydrophthalic acid, and (meth)acryloyloxypropyl hexahydrophthalic acid, and further preferred are (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxyethyl phthalic acid, (meth)acryloyloxyethyl hexahydrophthalic acid, (meth)acryloyloxypropyl phthalic acid, and (meth)acryloyloxypropyl hexahydrophthalic acid, and most preferred are (meth)acryloyloxyethyl phthalic acid and (meth)acryloyloxypropyl phthalic acid.

[0047] The content of the organic compound (B)-2 having an acidic group and a polymerizable group in the stereolithography composition of the present invention is preferably 0.1 to 10% by mass in the total amount of polymerizable monomers, and from the viewpoint of better color tone and water resistance of the cured product, it is more preferably 0.5 to 7.5% by mass, and even more preferably 1.0 to 5.0% by mass. The content of the organic compound (B)-2 having an acidic group and a polymerizable group is preferably 0.1 to 10% by mass in the entire stereolithography composition, and from the viewpoint of better color tone and water resistance of the cured product, it is more preferably 0.5 to 7.5% by mass, and even more preferably 1.0 to 5.0% by mass. In a preferred embodiment, from the viewpoint of better color tone and water resistance of the cured product, the content of the organic compound (B)-2 having an acidic group and a polymerizable group is preferably greater than the content of the organic compound (B)-1 having an acidic group and no polymerizable group.

[0048] The content of the organic compound (B) having an acidic group in the stereolithography composition of the present invention is preferably 0.1 to 10 mass %, more preferably 1.5 to 7 mass %, and even more preferably 1.7 to 5 mass %.

[0049] [Compound (C) having a phenol skeleton but no polymerizable group] The photo-lithography composition of the present invention contains a compound (C) having a phenol skeleton but no polymerizable group (hereinafter, simply referred to as "compound (C) having a phenol skeleton") in order to provide good modeling precision and to improve color tone. The compound (C) having a phenol skeleton absorbs the relatively weak light that is scattered or diffracted outside the irradiation range during photo-lithography, thereby improving modeling precision. The compound (C) having a phenol skeleton may be used alone or in combination of two or more kinds.

[0050] The compound (C) having a phenol skeleton is not particularly limited as long as it has at least one phenol group in the structure, and the benzene ring of the phenol group may have a substituent. Examples of the substituent include an alkyl group having 1 to 6 carbon atoms and an alkoxy group having 1 to 6 carbon atoms. The number of the substituents is not particularly limited and can be changed according to the number of the benzene rings, and may be, for example, 1 to 5, 1 to 4, or 1 to 3. As the compound (C) having a phenol skeleton, a phenol compound having only an aromatic monocyclic ring (benzene ring, biphenyl ring, triphenylmethyl ring, etc.) or an aromatic condensed bicyclic ring (naphthalene ring, pentalene ring, indene ring, indane ring, tetralin ring, azulene ring, etc.) as a cyclic structure is preferable, a phenol compound having only two or less benzene rings as a cyclic structure is more preferable, and a phenol compound having only one benzene ring as a cyclic structure is even more preferable. In one embodiment, the compound (C) having a phenol skeleton is not particularly limited, but is preferably a phenol compound having a molecular weight of less than 500, more preferably a phenol compound having a molecular weight of less than 300, and even more preferably a phenol compound having a molecular weight of less than 250.

[0051] Examples of the compound (C) having a phenol skeleton include phenol, pt-butylphenol, biphenol (4,4'-biphenol, 2,2'-biphenol, etc.), 2-phenylpropylphenol, 4-hydroxyphenol, 4-methoxyphenol, 2,6-di-t-butyl-4-methylphenol, 3,5-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-methoxyphenol, 3,5-di-t-butyl-4-methoxyphenol, 2,4,6-trimethylphenol, 2,6-di-isopropylphenol, 4-t-butylpyrocatechol, and naphthol (1-naphthol, 2-naphthol). Among these, from the viewpoints of good formability and small effect on color tone, pt-butylphenol, biphenol, 2-phenylpropylphenol, 4-methoxyphenol, 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-methoxyphenol, 2,4,6-trimethylphenol, 2,6-di-isopropylphenol, and naphthol are preferably used, and 4-methoxyphenol and 2,6-di-t-butyl-4-methylphenol are more preferably used in terms of further suppression of coloration.

[0052] The content of the compound (C) having a phenol skeleton in the stereolithography composition of the present invention is 0.5 to 500 parts by mass relative to 100 parts by mass of the organic compound (B) having an acidic group, from the viewpoint of excellent water resistance, and is preferably 5 to 250 parts by mass, more preferably 7 to 200 parts by mass, and even more preferably 10 to 100 parts by mass, from the viewpoint of excellent modeling precision and color tone of the cured product and more moderate flexibility of the cured product. The content of the compound (C) having a phenol skeleton is preferably 0.1 to 10% by mass in the entire stereolithography composition, and is more preferably 0.2 to 8% by mass, and even more preferably 0.3 to 5% by mass, from the viewpoint of excellent modeling precision and color tone of the cured product and more moderate flexibility of the cured product. Furthermore, the content of the compound (C) having a phenol skeleton in the photopolymerization composition of the present invention is preferably 1 to 800 parts by mass per 100 parts by mass of the organic compound (B)-1 having an acidic group and no polymerizable group in order to provide excellent water resistance, and is more preferably 10 to 700 parts by mass, and even more preferably 20 to 500 parts by mass in order to provide a cured product with better molding precision and color tone and with more appropriate flexibility.

[0053] [Photopolymerization initiator (D)] The photopolymerization initiator (D) used in the present invention can be selected from photopolymerization initiators used in general industrial fields, and among them, photopolymerization initiators used for dental purposes are preferred.

[0054] Examples of the photopolymerization initiator (D) include (bis)acylphosphine oxides, thioxanthones or quaternary ammonium salts of thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, α-aminoketone compounds, germanium compounds, etc. The photopolymerization initiator (D) may be used alone or in combination of two or more kinds.

[0055] Among these photopolymerization initiators (D), it is preferable to use at least one selected from the group consisting of (bis)acylphosphine oxides and α-diketones, which provides a stereolithography composition that is excellent in photocurability in the ultraviolet and visible light regions and exhibits sufficient photocurability when any of the light sources, such as a laser, a halogen lamp, a light-emitting diode (LED), and a xenon lamp, is used.

[0056] Among the (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, benzoyldi(2,6-dimethylphenyl)phosphonate, 2,4,6-trimethylbenzoylphenylphosphine oxide sodium salt, 2,4,6-trimethylbenzoylphenylphosphine oxide potassium salt, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide ammonium salt. Examples of bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide, etc. Furthermore, compounds described in JP-A-2000-159621 can be mentioned.

[0057] Among these (bis)acylphosphine oxides, it is particularly preferable to use 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and 2,4,6-trimethylbenzoylphenylphosphine oxide sodium salt as the photopolymerization initiator (D).

[0058] Examples of α-diketones include diacetyl, benzyl, camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4′-oxybenzyl, and acenaphthenequinone. Among these, camphorquinone is particularly preferred when a light source in the visible light range is used.

[0059] Examples of the germanium compound include monoacylgermanium compounds such as benzoyltrimethylgermanium(IV); and diacylgermanium compounds such as dibenzoyldiethylgermanium or bis(4-methoxybenzoyl)-diethylgermanium.

[0060] The content of the photopolymerization initiator (D) in the optical molding composition of the present invention is not particularly limited as long as the effects of the present invention are exhibited, but from the viewpoint of the curability of the obtained optical molding composition, the content of the photopolymerization initiator (D) is preferably 0.1 to 10 parts by mass per 100 parts by mass of the total amount of the polymerizable monomers. If the content of the photopolymerization initiator (D) is less than 0.1 parts by mass, the polymerization may not proceed sufficiently, and a cured product may not be obtained. The content of the photopolymerization initiator (D) is more preferably 0.5 parts by mass or more, and even more preferably 1.0 parts by mass or more, per 100 parts by mass of the total amount.

[0061] The photopolymerization composition of the present invention is not particularly limited as long as it contains the above-mentioned polymerizable monomer (A) not having an acidic group, organic compound (B) having an acidic group, compound (C) having a phenol skeleton, and photopolymerization initiator (D), and can be produced in accordance with a known method.

[0062] The stereolithography composition of the present invention may contain a polymerization accelerator for the purpose of improving photocurability, within the scope of the present invention. Examples of the polymerization accelerator include organic compounds having an alkenyl group such as thioxanthone, polydiene, and unsaturated fatty acid (excluding those included in the organic compound (B)-1 having an acidic group and no polymerizable group); and amine compounds such as aminobenzoic acid esters such as ethyl 4-(N,N-dimethylamino)benzoate, methyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate, 2-(methacryloyloxy)ethyl 4-(N,N-dimethylamino)benzoate, and butyl 4-(N,N-dimethylamino)benzoate. Among these, at least one selected from the group consisting of organic compounds having an alkenyl group such as thioxanthone, polydiene, and unsaturated fatty acid is preferably used from the viewpoint of imparting excellent curability to the stereolithography composition.

[0063] The stereolithography composition of the present invention may further contain a filler in order to adjust the paste properties or to modify the surface properties or mechanical strength of the cured product of the stereolithography composition. Examples of the filler include organic fillers, inorganic fillers, and organic-inorganic composite fillers. One type of filler may be used alone, or two or more types may be used in combination.

[0064] Examples of the organic filler material include polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, crosslinked polymethyl methacrylate, crosslinked polyethyl methacrylate, polyester, polyamide, polycarbonate, polyphenylene ether, polyoxymethylene, polyvinyl chloride, polystyrene, polyethylene, polypropylene, chloroprene rubber, nitrile rubber, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-styrene-butadiene copolymer. These may be used alone or in combination of two or more. The shape of the organic filler is not particularly limited, and the particle size of the filler can be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the obtained stereolithography composition, the average particle size of the organic filler is preferably 0.001 to 50 μm, more preferably 0.001 to 10 μm, and even more preferably 0.001 to 1.0 μm.

[0065] Examples of inorganic filler materials include quartz, silica, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, and strontium calcium fluoroaluminosilicate glass. These may also be used alone or in combination of two or more. The shape of the inorganic filler is not particularly limited, and irregular fillers or spherical fillers, etc., may be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the resulting stereolithography composition, the average particle size of the inorganic filler is preferably from 0.001 to 50 μm, more preferably from 0.001 to 10 μm, and even more preferably from 0.001 to 1.0 μm.

[0066] Polymers can be added to the stereolithography composition of the present invention for the purpose of improving flexibility, fluidity, etc., within the scope of the present invention. For example, natural rubber, synthetic polyisoprene rubber, liquid polyisoprene rubber and its hydrogenated product, polybutadiene rubber, liquid polybutadiene rubber and its hydrogenated product, styrene-butadiene rubber, chloroprene rubber, ethylene-propylene rubber, acrylic rubber, isoprene-isobutylene rubber, acrylonitrile-butadiene rubber, or styrene-based elastomers can be added. Specific examples of other polymers that can be added include polystyrene-polyisoprene-polystyrene block copolymers, polystyrene-polybutadiene-polystyrene block copolymers, poly(α-methylstyrene)-polybutadiene-poly(α-methylstyrene) block copolymers, poly(p-methylstyrene)-polybutadiene-poly(p-methylstyrene) block copolymers, or hydrogenated products thereof. The polymers may be used alone or in combination of two or more types.

[0067] The stereolithography composition of the present invention may contain a softener as necessary. Examples of the softener include petroleum-based softeners such as paraffinic, naphthenic, and aromatic process oils, and vegetable oil-based softeners such as paraffin, peanut oil, and rosin. These softeners may be used alone or in combination of two or more. The content of the softener is not particularly limited as long as it does not impair the gist of the present invention, but is usually 200 parts by mass or less, preferably 100 parts by mass or less, relative to 100 parts by mass of the total amount of the polymerizable monomers.

[0068] The stereolithography composition of the present invention may contain a chemical polymerization initiator for the purpose of improving curability, within the scope of the present invention. As the chemical polymerization initiator, organic peroxides and azo compounds are preferably used. The organic peroxides and azo compounds used as the chemical polymerization initiator are not particularly limited, and known ones can be used. Representative organic peroxides include ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates. The chemical polymerization initiator may be used alone or in combination of two or more kinds.

[0069] In addition, the stereolithography composition of the present invention may contain a known stabilizer for the purpose of suppressing deterioration or adjusting photocurability. Examples of the stabilizer include polymerization inhibitors, ultraviolet absorbers, and antioxidants. The stabilizer may be used alone or in combination of two or more.

[0070] In addition, the stereolithography composition of the present invention may contain known additives for the purpose of adjusting the color tone or the paste properties. Examples of the additives include colorants (pigments, dyes), organic solvents, and thickeners. The additives may be used alone or in combination of two or more.

[0071] The stereolithography composition of the present invention can obtain a molded object that is easy to mold and has excellent toughness, water resistance, and color tone when molded by stereolithography (especially suspended liquid tank stereolithography). It can also be applied to inkjet stereolithography. Therefore, the stereolithography composition of the present invention and its cured product can be applied to applications in which such advantages are utilized, and can be applied to intraoral applications such as dental materials and sleep disorder treatment materials. As a dental material, it is particularly suitable for dental mouthpieces (orthodontic aligners, night guards, dental splints, etc.) and denture base materials. As a sleep disorder treatment material, it is particularly suitable for sleep apnea syndrome treatment devices (oral appliances, etc.). Furthermore, the stereolithography composition of the present invention can be suitably used as a protective gear against external forces in sports, such as a mouthguard, in addition to dental treatment applications and sleep disorder treatment applications such as dental mouthpieces and denture base materials. The shape of the cured product using the stereolithography composition of the present invention can be changed according to each application. Furthermore, the type and content of each component (polymerizable monomer (A) having no acidic group, organic compound (B) having an acidic group, compound (C) having a phenol skeleton, photopolymerization initiator (D), and various other components (chemical polymerization initiator, polymerization accelerator, filler, polymer, softener, stabilizer, additives, etc.)) of the photopolymerization composition of the present invention can be adjusted as needed for each application, such as a dental mouthpiece or denture base material.

[0072] The photopolymerization composition of the present invention can be used in a variety of applications by taking advantage of its properties, particularly the property that when cured with light, it can give three-dimensional objects having a small volumetric shrinkage rate and excellent modeling precision, and also having excellent toughness, water resistance, and color tone of the cured product, as well as other cured products. For example, it can be used in the production of three-dimensional objects by optical three-dimensional modeling methods, the production of various photopolymerization compositions such as film-like objects or molded objects by casting molding, casting, etc., and for coating and vacuum molding dies, etc.

[0073] Among these, the photopolymerization composition of the present invention is suitable for use in the above-mentioned optical three-dimensional modeling method, and in this case, it is possible to smoothly produce a three-dimensional object that has excellent modeling precision, toughness, water resistance, and color tone while maintaining a small volumetric shrinkage rate upon photocuring.

[0074] Another embodiment of the present invention is a method for producing a three-dimensional object by a stereolithography method using any one of the above-mentioned compositions for stereolithography. As the stereolithography method, a suspended liquid tank stereolithography method is preferable.

[0075] When performing optical 3D modeling (particularly, lift-type liquid tank optical modeling) using the optical modeling composition of the present invention, any of the conventionally known optical 3D modeling methods and devices (for example, optical modeling machines such as DIGITALWAX (registered trademark) 020D manufactured by DWS) can be used. The optical 3D modeling method and device are not particularly limited, but from the viewpoint of the viscosity of the optical modeling composition, the optical modeling composition of the present invention is particularly suitable for a lift-type optical 3D modeling device (lift-type liquid tank optical modeling device). Among them, in the present invention, it is preferable to use active energy rays as the light energy for curing the resin. The "active energy rays" refer to energy rays that can cure the optical modeling composition, such as ultraviolet rays, electron beams, X-rays, radiation, and high frequency waves. For example, the active energy rays may be ultraviolet rays having a wavelength of 300 to 420 nm. Examples of light sources for active energy rays include lasers such as Ar lasers and He-Cd lasers; and lighting such as halogen lamps, xenon lamps, metal halide lamps, LEDs, mercury lamps, and fluorescent lamps, with lasers being particularly preferred. When a laser is used as a light source, it is possible to increase the energy level and shorten the modeling time, and furthermore, by utilizing the excellent focusing properties of the laser beam, a three-dimensional object with high modeling accuracy can be obtained.

[0076] As described above, when performing optical three-dimensional modeling using the optical modeling composition of the present invention, any of the conventionally known methods and conventionally known optical modeling system devices can be adopted and are not particularly limited, but a representative example of the optical three-dimensional modeling method preferably used in the present invention is a method of finally obtaining a desired three-dimensional object by repeating a process of selectively irradiating the optical modeling composition with an active energy ray to form a cured layer having a desired pattern, and a process of supplying an uncured liquid optical modeling composition and similarly irradiating it with an active energy ray to form a new cured layer continuous with the above cured layer and laminating them. The three-dimensional object obtained by this process may be used as it is, or may be used after further performing post-cure by irradiation with light or post-cure by heat, etc., in some cases to further improve its mechanical properties or shape stability.

[0077] The flexural modulus of the cured product of the stereolithography composition of the present invention is preferably in the range of 0.3 to 3.0 GPa, more preferably in the range of 0.5 to 2.5 GPa, and even more preferably in the range of 0.8 to 2.0 GPa. When the flexural modulus of the cured product is 2.0 GPa or less, the cured product has a flexible property, and when made into a dental mouthpiece, it has good conformity to the teeth, so that it is comfortable to wear, and is less likely to fall off due to bruxism (teeth grinding) during sleep at night. In addition, the flexural strength of the cured product of the stereolithography composition of the present invention is preferably 30 MPa or more, more preferably 40 MPa or more, and even more preferably 50 MPa or more. The upper limit of the flexural strength is usually 100 MPa or less. The flexural modulus and flexural strength can be measured by the method described in the Examples below.

[0078] The structure, shape, size, etc. of the three-dimensional object obtained by the optical three-dimensional modeling method are not particularly limited and can be determined according to each application. Representative application fields of the optical three-dimensional modeling method of the present invention include the production of models for verifying the appearance design during the design process, models for checking the functionality of parts, resin molds for producing casting molds, base models for producing metal molds, direct molds for prototype metal molds, etc. More specifically, the production of models for precision parts, electric and electronic parts, furniture, architectural structures, automotive parts, various containers, castings, metal molds, mother molds, etc., or models for processing, etc., can be mentioned. EXAMPLES

[0079] Next, the present invention will be described in more detail with reference to examples. However, the present invention is not limited to these examples, and many modifications can be made by those having ordinary skill in the art within the scope of the technical concept of the present invention.

[0080] Each component used in the stereolithography compositions according to the Examples and Comparative Examples will be explained below together with its abbreviation.

[0081] [Polymerizable monomer (A) having no acidic group] [Monofunctional polymerizable monomer (A)-1a having a cyclic structure] EPPA: Ethoxylated o-phenylphenol acrylate (A-LEN-10, manufactured by Shin-Nakamura Chemical Co., Ltd.) POBA: m-phenoxybenzyl acrylate (Kyoeisha Chemical Co., Ltd.) PMA: Phenyl methacrylate (Tokyo Chemical Industry Co., Ltd.) PMPMA: Pentamethylpiperidinyl methacrylate (Tokyo Chemical Industry Co., Ltd.)

[0082] [Polyfunctional polymerizable monomer (A)-2a having a urethane bond] HTM: 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (Kyoeisha Chemical Co., Ltd.) The urethane-modified (meth)acrylic compounds (A)-2a-1 and (A)-2a-2 produced in Synthesis Examples 1 and 2 described below were used.

[0083] [Polyfunctional polymerizable monomer (A)-2b having no urethane bond] D2.6E: 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0084] [Organic compounds having acidic groups (B)] [Organic compound (B)-1 having an acidic group and no polymerizable group] LA: DL-lactic acid (Fujifilm Wako Pure Chemical Industries, Ltd.) BA: Benzoic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) IE2: Isoeicosanedioic acid (Okamura Oil Mills)

[0085] [Organic compound (B)-2 having an acidic group and a polymerizable group] AEP: 2-acryloyloxyethyl phthalate (Kyoeisha Chemical Co., Ltd.) AES: 2-acryloyloxyethyl succinic acid (Kyoeisha Chemical Co., Ltd.)

[0086] [Compounds with a phenol skeleton (C)] MBP: 2,6-di-t-butyl-4-methylphenol MPH: 4-Methoxyphenol

[0087] [Photopolymerization initiator (D)] TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide BAPO: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide

[0088] <Synthesis Example 1> [Production of urethane-modified (meth)acrylic compound (A)-2a-1] (1) 250 g of isophorone diisocyanate and 0.15 g of di-n-butyltin dilaurate were added to a 5 L four-neck flask equipped with a stirrer, a temperature controller, a thermometer, and a condenser, and the mixture was heated to 70° C. with stirring. (2) On the other hand, 2500 g of polyester polyol ("Kuraray Polyol (registered trademark) P-2030" manufactured by Kuraray Co., Ltd.; polyol consisting of isophthalic acid and 3-methyl-1,5-pentanediol, weight average molecular weight Mw: 2000) was added to a dropping funnel equipped with a side tube, and the liquid in this dropping funnel was dropped into the flask in (1) above. The solution in the flask in (1) above was stirred and dropped at a constant rate over 4 hours while maintaining the internal temperature of the flask at 65 to 75°C. After the dropping was completed, the mixture was stirred at the same temperature for 2 hours to react. (3) Next, a solution in which 150 g of 2-hydroxyethyl acrylate and 0.4 g of hydroquinone monomethyl ether were uniformly dissolved in another dropping funnel was added dropwise at a constant rate over 2 hours while maintaining the internal temperature of the flask at 55 to 65°C, and then the temperature of the solution in the flask was maintained at 70 to 80°C while reacting for 4 hours to obtain a urethane-modified (meth)acrylic compound (A)-2a-1. The weight average molecular weight Mw of the urethane-modified (meth)acrylic compound (A)-2a-1 was 2700 by GPC analysis.

[0089] <Synthesis Example 2> [Production of urethane-modified (meth)acrylic compound (A)-2a-2] (1) 250 g of isophorone diisocyanate and 0.15 g of di-n-butyltin dilaurate were added to a 5 L four-neck flask equipped with a stirrer, a temperature controller, a thermometer, and a condenser, and the mixture was heated to 70° C. with stirring. (2) On the other hand, 2500 g of polyester polyol ("Kuraray Polyol (registered trademark) P-2050" manufactured by Kuraray Co., Ltd.; polyol consisting of sebacic acid and 3-methyl-1,5-pentanediol, weight average molecular weight Mw: 2000) was added to a dropping funnel equipped with a side tube, and the liquid in this dropping funnel was dropped into the flask in (1) above. The solution in the flask in (1) above was stirred and dropped at a constant rate over 4 hours while maintaining the internal temperature of the flask at 65 to 75°C. After the dropping was completed, the mixture was stirred at the same temperature for 2 hours to react. (3) Next, a solution in which 150 g of 2-hydroxyethyl acrylate and 0.4 g of hydroquinone monomethyl ether were uniformly dissolved in another dropping funnel was added dropwise at a constant rate over 2 hours while maintaining the internal temperature of the flask at 55-65°C, and then the solution was reacted for 4 hours while maintaining the temperature of the solution in the flask at 70-80°C to obtain a urethane-modified (meth)acrylic compound (A)-2a-2. The weight average molecular weight Mw of the urethane-modified (meth)acrylic compound (A)-2a-2 was 2600 by GPC analysis.

[0090] [Examples 1 to 11 and Comparative Examples 1 to 4] The components shown in Tables 1 and 2 were mixed at room temperature (20°C ± 15°C, JIS (Japanese Industrial Standards) Z 8703:1983) in the amounts shown in Tables 1 and 2 to prepare pastes as stereolithography compositions according to Examples 1 to 11 and Comparative Examples 1 to 4.

[0091] <Formability> For each of the examples and comparative examples, a photopolymerization machine (DIGITALWAX (registered trademark) 020D manufactured by DWS) was used to mold test pieces measuring 3.3 mm thick x 10.0 mm wide x 64 mm long at a molding pitch of 50 μm and a laser scanning speed of 4300 mm / sec (n=5). When a sheet with the correct dimensions could be molded, it was marked as "○" for "moldable", and when even one three-dimensional object could not be obtained, it was marked as "×" for "not moldable". The molded test pieces were used to carry out the various evaluations described below.

[0092] <Toughness (flexural modulus, flexural strength, break point displacement)> For the cured product of the stereolithography composition according to each Example and Comparative Example, a test piece (length 64.0 mm, width 10.0 mm, thickness 3.3 mm) with dimensions described in JIS T 6501:2012 (acrylic resin for denture base) was prepared at a modeling pitch of 50 μm and a laser scanning speed of 4300 mm / sec. The test piece was stored in air for one day, and then a bending strength test was performed to evaluate the test piece, which was taken as the initial value. Specifically, a bending strength test was performed (n=5) using a universal testing machine (Shimadzu Corporation, Autograph AG-I 100 kN) with a support distance of 50 mm and a crosshead speed of 5 mm / min. The average values ​​of the measured values ​​are shown in Tables 1 and 2. The bending modulus of the test piece is preferably in the range of 0.3 to 3.0 GPa, more preferably in the range of 0.5 to 2.5 GPa, and even more preferably in the range of 0.8 to 2.0 GPa. The bending strength is preferably 30 MPa or more, more preferably 40 MPa or more, and even more preferably 50 MPa or more. As for the displacement at break, it is preferable that the specimen does not break. When the specimen does not break until the end or breaks at a displacement of 20 mm or more, the flexibility is evaluated as "good" (○), when the specimen breaks at a displacement of more than 10 mm but less than 20 mm, the flexibility is evaluated as "medium" (△), and when the specimen breaks at a displacement of 10 mm or less, the flexibility is evaluated as "poor" (×).

[0093] <Water resistance> The cured products of the stereolithography compositions according to each Example and Comparative Example, which were prepared in the same manner as the cured products prepared in the toughness measurement, were immersed in water at 37°C for 168 hours, and the flexural strength was measured in the same manner as in the above flexural strength test (n=5). The measurement result of the flexural strength in the above toughness was taken as the initial flexural strength, and the rate of change (decrease) of the flexural strength after 168 hours of immersion in water at 37°C relative to the initial flexural strength was calculated. If the rate of change (decrease) of the flexural strength is 10% or less, the water resistance is excellent, and if it is 7% or less, the water resistance is even more excellent. The average values ​​of the calculated values ​​are shown in Tables 1 and 2. In Tables 1 and 2, the flexural strength after immersion in water at 37°C for 168 hours is shown as "flexural strength after immersion". Rate of change (decrease) in bending strength (%) = [{initial bending strength (MPa) - bending strength after 168 hours in 37°C water (MPa)} / initial bending strength (MPa)] x 100

[0094] <color tone> For the stereolithography compositions according to each Example and Comparative Example, a disk-shaped object having a diameter of 15.0 mm and a thickness of 1.0 mm was produced in the same manner as described above, with a modeling pitch of 50 μm and a laser scanning speed of 4300 mm / sec. The obtained object was washed with ethanol to remove unpolymerized monomers, and then subjected to secondary polymerization for 5 minutes using an LED polymerization device for dental laboratories, Alpha Light V (manufactured by Morita Tokyo Seisakusho Co., Ltd.), to obtain a cured product. The obtained cured product was polished with silicon carbide paper No. 1000, and then polished with a dental lapping film (manufactured by 3M Co.), and the yellowness b* value of the cured product after polishing was measured using a spectrophotometer (manufactured by Konica Minolta, Inc., SPECTROPHOTOMETER CM-3610A, corresponding to JIS Z 8722:2009, condition c, D65 light source), and the average value was obtained (n=5). If the b* value exceeds 10, it is determined that the coloring is large and the color tone is poor.

[0095] [Table 1]

[0096] [Table 2]

[0097] As shown in Tables 1 and 2, the stereolithography compositions of Examples 1 to 11 had excellent moldability, and the cured products thereof had excellent toughness, water resistance, and color tone. In particular, the stereolithography compositions of Examples 1 to 11 had excellent moldability, and the toughness and water resistance of the cured products were superior to the compositions of Comparative Examples 2 to 4, which had an inappropriate content of the compound (C) having a phenol skeleton. In addition, the color tone of the cured products of the stereolithography compositions of Examples 1 to 11 was superior to the composition of Comparative Example 1, which did not have the organic compound (B) having an acidic group, and the compositions of Comparative Examples 2 to 4, which had an inappropriate content of the compound (C) having a phenol skeleton. [Industrial Applicability]

[0098] The photopolymerization composition of the present invention, when used for photopolymerization, can give a three-dimensional object that is excellent in formability as well as toughness, water resistance and color tone, and is particularly suitable for dental mouthpieces and denture base materials.

Claims

1. A photopolymerization composition comprising: The optical molding composition contains a polymerizable monomer (A) having no acidic group, an organic compound (B) having an acidic group, a compound (C) having no polymerizable group and having a phenol skeleton (excluding those contained in the organic compound (B) having an acidic group), and a photopolymerization initiator (D); The polymerizable monomer (A) contains a monofunctional polymerizable monomer (A)-1 and a polyfunctional polymerizable monomer (A)-2, the content of the compound (C) having a phenol skeleton is 0.5 to 500 parts by mass relative to 100 parts by mass of the organic compound (B) having an acidic group, The stereolithography composition is used to produce a disk-shaped object having a diameter of 15.0 mm and a thickness of 1.0 mm at a modeling pitch of 50 μm and a laser scanning speed of 4,300 mm / sec. The object is then subjected to secondary polymerization to form a cured product, and the cured product has a b* value of 10 or less as measured using a spectrophotometer (SPECTROPHOTOMETER CM-3610A, manufactured by Konica Minolta, Inc., corresponding to JIS Z 8722:2009, condition c, D65 light source).

2. 2. The stereolithography composition according to claim 1, wherein the monofunctional polymerizable monomer (A)-1 contains a monofunctional polymerizable monomer (A)-1a having a cyclic structure.

3. 2. The optical molding composition according to claim 1, wherein the polyfunctional polymerizable monomer (A)-2 is a polyfunctional polymerizable monomer (A)-2a having a urethane bond.

4. The optical molding composition according to claim 3, wherein the polyfunctional polymerizable monomer (A)-2a having a urethane bond is a (meth)acrylate having, in one molecule, at least one structure selected from the group consisting of polyester, polycarbonate, polyurethane, polyether, polyconjugated diene, and hydrogenated polyconjugated diene, and a urethane bond.

5. The optical molding composition according to claim 3, wherein the polyfunctional polymerizable monomer (A)-2a having a urethane bond is at least one polyol moiety selected from the group consisting of polyesters, polycarbonates, polyurethanes, polyethers, polyconjugated dienes, and hydrogenated polyconjugated dienes, each of which has a structure derived from an aliphatic diol unit having 4 to 18 carbon atoms and a branched structure in one molecule, and a (meth)acrylate having a urethane bond.

6. The photopolymerization composition according to any one of claims 1 to 5, wherein the organic compound (B) having an acidic group contains an organic compound (B)-1 having an acidic group and no polymerizable group.

7. The photopolymerization composition according to claim 6, wherein the organic compound (B)-1 having an acidic group and no polymerizable group is at least one selected from the group consisting of a carboxylic acid compound having only one carboxy group as the acidic group, a dicarboxylic acid compound having only two carboxy groups as the acidic groups, and a carboxylic acid compound having a hydroxyl group and a carboxy group.

8. The photopolymerization composition according to claim 6, wherein the organic compound (B)-1 having an acidic group and no polymerizable group is at least one selected from the group consisting of isoeicosane diacid, DL-lactic acid, malic acid, tartaric acid, citric acid, and benzoic acid.

9. The photopolymerization composition according to any one of claims 1 to 8, wherein the organic compound (B) having an acidic group contains an organic compound (B)-2 having an acidic group and a polymerizable group.

10. 10. The optical molding composition according to claim 9, wherein the organic compound (B)-2 having an acidic group and a polymerizable group is a carboxyl group-containing polymerizable monomer.

11. The photopolymerization composition according to claim 10, wherein the carboxy group-containing polymerizable monomer is at least one selected from the group consisting of (meth)acryloyloxyethyl succinic acid, (meth)acryloyloxyethyl phthalic acid, (meth)acryloyloxyethyl hexahydrophthalic acid, (meth)acryloyloxypropyl phthalic acid, and (meth)acryloyloxypropyl hexahydrophthalic acid.

12. The photopolymerization composition according to any one of claims 1 to 11, wherein the compound (C) having a phenol skeleton is a phenol compound having only an aromatic monocyclic ring or an aromatic condensed bicyclic ring as a cyclic structure.

13. The stereolithography composition according to any one of claims 1 to 11, wherein the compound (C) having a phenol skeleton is at least one selected from the group consisting of p-t-butylphenol, biphenol, 2-phenylpropylphenol, 4-methoxyphenol, 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-methoxyphenol, 2,4,6-trimethylphenol, 2,6-di-isopropylphenol, and naphthol.

14. A dental material comprising a cured product of the stereolithography composition according to any one of claims 1 to 13.

15. A dental mouthpiece comprising a cured product of the stereolithography composition according to any one of claims 1 to 13.

16. A denture base material comprising a cured product of the stereolithography composition according to any one of claims 1 to 13.

17. A material for treating a sleep disorder, comprising a cured product of the composition for stereolithography according to any one of claims 1 to 13.

18. A method for producing a three-dimensional object by a stereolithography method, using the composition for stereolithography according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Stereoscopic figure drawing device

    JP1981144478A

  • Optical shaping method

    JP1985247515A

  • Dental polymerizable composition

    JP2014189504A

  • Resin composition for optical three-dimensional molding, and three-dimensional molded article

    JP2015010168A

  • Dental mill blank assembly

    JP2018076272A